(untitled) (Minerva, 2019)
Review: Francesco De Martino-Carmen Morenilla (eds.), Teatro y sociedad en la Antigüedad clásica. A la sombra de los héroes, Bari, Levante Editori, 2014, 486 pp. ISBN. 978-88-7949-638-4